Efficacy and bleeding profile of a combined oral contraceptive containing oestradiol valerate/dienogest: A pooled analysis of three studies conducted in North America and Europe. (August 2013) - Nelson, Anita; Parke, Susanne; Makalova, Dagmar; Serrani, Marco; Palacios, Santiago; Mellinger, Uwe
Abstract Objective To summarise all clinical data on the contraceptive efficacy and bleeding profile associated with an oestradiol valerate (E2V) and dienogest (DNG) [E2V/DNG] combined oral contraceptive (COC) derived from Phase III trials. Methods Pooled analysis of three large-scale multicentre trials conducted in healthy women who received oral E2V/DNG for 7 to 28 cycles (28-day cycles). Results A total of 2266 women were included in this analysis. Overall, 19 pregnancies occurred over 13 cycles during 880, 950 days of relevant exposure (Pearl Index [PI] of 0.79; upper limit of the two-sided 95% confidence interval [CI]: 1.23). Ten pregnancies attributed to method failure came about during 871, 091 days of relevant exposure (adjusted PI of 0.42; upper limit of the two-sided 95% CI: 0.77). In women aged 18 to 35 years (n = 1687), the corresponding PI and adjusted PI were 1.01 (upper limit of the two-sided 95% CI: 1.59) and 0.51 (upper limit of the two-sided 95% CI: 0.97), respectively. In the first 13 cycles of treatment, 76 to 81% of women experienced scheduled withdrawal bleeding, and 13 to 23% experienced intracyclic bleeding. Conclusions E2V/DNG provides reliable contraceptive efficacy in women aged 18 to 50 years.